Methane in Zackenberg Valley, NE Greenland: multidecadal growing season fluxes of a high-Arctic tundra - J. H. Scheller (Copernicus Publications, 2021)
The carbon balance of high-latitude terrestrial ecosystems plays an essential role in the atmospheric concentration of trace gases, including carbon dioxide (CO2) and methane (CH4). Increasing atmospheric methane levels have contributed to ∼ 20 % of the observed global warming since the pre-industrial era. Rising temperatures in the Arctic are expected to promote the release of methane from Arctic ecosystems. Still, existing methane flux measurement efforts are sparse and highly scattered, and further attempts to assess the landscape fluxes over multiple years are needed.